Penambahan Zat Aditif Bestmittel Dengan Dosis 0,5% dan Pengaruhnya Terhadap Kuat Tekan Beton - Salsabilla Salsabilla; Ermiyati Ermiyati; Haji Gussyafri; Andre Novan; Nurdin Nurdin (SAINSTEK, 2025)
Concrete is one of the main construction materials widely used in infrastructure development due to its high compressive strength and good durability. However, achieving optimum compressive strength in concrete requires a relatively long curing time, around 28 days. To overcome this issue, additives such as Bestmittel are used, which function to accelerate the hardening process and increase the compressive strength of concrete at an early age. This study aims to determine the effect of adding 0.5% Bestmittel on the compressive strength of concrete at curing ages of 3, 5, 7, 15, and 28 days. The specimens used were cylindrical with a diameter of 15 cm and a height of 30 cm, and three samples were prepared for each variation. Based on the test results, the compressive strength of normal concrete at 28 days was 26.31 MPa, while the compressive strength of concrete with Bestmittel at 3, 5, 7, 15, and 28 days was 20.47 MPa, 25.65 MPa, 25.94 MPa, 27.63 MPa, and 32.16 MPa, respectively. At 7 days, concrete with Bestmittel almost reached the strength of normal concrete at 28 days, with a percentage of 98.58%, and at 15 and 28 days it exceeded the strength of normal concrete with percentages of 105.03% and 122.24%, respectively. The results show that the addition of 0.5% Bestmittel is effective in accelerating early-age strength gain, making it highly suitable for use in construction projects that require high strength within a relatively short time.